The green gap framework: Understanding non and low use of urban greenspaces - Avril Johnstone; Rob Bushby; Ruth F Hunter; Sarah Rodgers; Catharine Ward Thompson; Andrew J Williams; Benedict W Wheeler; Richard Mitchell (Landscape and Urban Planning, 2026)

An interdisciplinary, co-teaching approach to a course in urban social-ecological systems - Vikki L. Rodgers; Stephen Deets; Sarah Foster; Paul Schmitz; Megan Way (Urban Ecosystems, 2025)

Development of an open-source carbon footprint calculator of the UK craft brewing value chain - Alexander L. Bowler; Sarah Rodgers; Fanran Meng; Jon McKechnie; David J. Cook; Nicholas J. Watson (Journal of Cleaner Production, 2024)

Bayesian and ultrasonic sensor aided multi-objective optimisation for sustainable clean-in-place processes - Alexander L. Bowler; Sarah Rodgers; David J. Cook; Nicholas J. Watson (Food and Bioproducts Processing, 2023)

Typha (Cattail) Invasion in North American Wetlands: Biology, Regional Problems, Impacts, Ecosystem Services, and Management - Sheel Bansal; Shane C. Lishawa; Sue Newman; Brian A. Tangen; Douglas Wilcox; Dennis Albert; Michael J. Anteau; Michael J. Chimney; Ryann L. Cressey; Edward DeKeyser; Kenneth J. Elgersma; Sarah A. Finkelstein; et al. (Wetlands, 2019)

Analysis of novel domain-specific mutations in the zebrafish ndr2/cyclops gene generated using CRISPR-Cas9 RNPs - Ashley N. Turner; Reagan S. Andersen; Ivy E. Bookout; Lauren N. Brashear; James C. Davis; David M. Gahan; John P. Gotham; Baraa A. Hijaz; Ashish S. Kaushik; Jordan B. Mcgill; Victoria L. Miller; Zachariah P. Moseley; et al. (Journal of Genetics, 2018)

The duality of ocean acidification as a resource and a stressor - Sean D. Connell; Zoë A. Doubleday; Nicole R. Foster; Sarah B. Hamlyn; Christopher D. G. Harley; Brian Helmuth; Brendan P. Kelaher; Ivan Nagelkerken; Kirsten L. Rodgers; Gianluca Sarà; Bayden D. Russell (Ecology, 2018)
Ecologically dominant species often define ecosystem states, but as human disturbances intensify, their subordinate counterparts increasingly displace them. We consider the duality of disturbance by examining how environmental drivers can simultaneously act as a stressor to dominant species and as a resource to subordinates. Using a model ecosystem, we demonstrate that CO 2 ‐driven interactions between species can account for such reversals in dominance; i.e., the displacement of dominants (kelp forests) by subordinates (turf algae). We established that CO 2 enrichment had a direct positive effect on productivity of turfs, but a negligible effect on kelp. CO 2 enrichment further suppressed the abundance and feeding rate of the primary grazer of turfs (sea urchins), but had an opposite effect on the minor grazer (gastropods). Thus, boosted production of subordinate producers, exacerbated by a net reduction in its consumption by primary grazers, accounts for community change (i.e., turf displacing kelp). Ecosystem collapse, therefore, is more likely when resource enrichment alters competitive dominance of producers, and consumers fail to compensate. By recognizing such duality in the responses of interacting species to disturbance, which may stabilize or exacerbate change, we can begin to understand how intensifying human disturbances determine whether or not ecosystems undergo phase shifts.

Carbon dynamics in a 60 year fallowed loamy-sand soil compared to that in a 60 year permanent arable or permanent grassland UK soil - Yuping Wu; Sarah Kemmitt; Rodger P. White; Jianming Xu; Philip C. Brookes (Plant and Soil, 2012)

Improving fluorometry as a source tracking method to detect human fecal contamination - Peter G. Hartel; Jennifer L. McDonald; Lisa C. Gentit; Sarah N. J. Hemmings; Karen Rodgers; Katy A. Smith; Carolyn N. Belcher; Robin L. Kuntz; Yaritza Rivera-Torres; Ernesto Otero; Eduardo C. Schröder (Estuaries and Coasts, 2007)